Noise Suppression in Low-Light Images through Joint Denoising and Demosaicing - Chatterjee, Priyam; Joshi, Neel; Kang, Sing Bing; Matsushita, Yasuyuki (CVPR '11 Proceedings of the 2011 IEEE Conference on Computer Vision and Pattern Recognition, 2011)
We address the effects of noise in low-light images. Color images are usually captured by a sensor with a color filter array (CFA) requiring a demosaicing process to generate a full color image. The captured images typically have low signal-to-noise ratio, and the demosaicing step further corrupts the image, which we show to be the leading cause of visually objectionable random noise patterns (splotches). To avoid this problem, we propose a combined framework of denoising and demosaicing, where we use information about the image inferred in the denoising step to perform demosaicing. Our experiments show that such a framework results in sharper low-light images that are devoid of splotches and other noise artifacts.